2022
DOI: 10.1136/bmjopen-2022-062170
|View full text |Cite
|
Sign up to set email alerts
|

Association of oral health knowledge, self-efficacy and behaviours with oral health-related quality of life in Chinese primary school children: a cross-sectional study

Abstract: ObjectiveAchieving good oral health-related quality of life (OHRQOL) is of particular concern in children. The inter-relations among oral health knowledge, self-efficacy, behaviours and OHRQOL in children groups remain unclear. This study aimed to explore the inter-relations between these oral health behaviour-related factors and OHRQOL in primary school children.MethodsIn this cross-sectional study, 651 children in grades 2 and 3 were recruited in October 2020 from two primary schools in Minhang District, Sha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 73 publications
0
4
1
Order By: Relevance
“…In the fsQCA positive solution, the higher coverage solution (C1 in Table 4 ) show that individual self-efficacy, oral knowledge and attitude can be considered important conditions affecting OHRQoL, but the results do not reflect the impact of practice. This is slightly different from previous studies 61 . The possible reason is that Chinese college students in this study are still in the sensitive period of constructing oral health practice, have strong plasticity, and are influenced by knowledge and attitude.…”
Section: Discussioncontrasting
confidence: 99%
“…In the fsQCA positive solution, the higher coverage solution (C1 in Table 4 ) show that individual self-efficacy, oral knowledge and attitude can be considered important conditions affecting OHRQoL, but the results do not reflect the impact of practice. This is slightly different from previous studies 61 . The possible reason is that Chinese college students in this study are still in the sensitive period of constructing oral health practice, have strong plasticity, and are influenced by knowledge and attitude.…”
Section: Discussioncontrasting
confidence: 99%
“…In our study, approximately one-fifth of the sample qualified for manifest to moderate DF/A [ 51 ]. According to expectations, OH-SE was positively correlated with OHRQoL, self-perceived dental condition, satisfaction with general health, number of annual dentist appointments, and socioeconomic status, confirming that a more pronounced OH-SE is associated with greater quality of life, as well as overall health in general and oral health specifically [ 3 , 14 ]. Additionally, significant negative correlations were found between OH-SE and DF/A, as well as OH-SE and the number of canceled dentist appointments due to DF/A (trend level), suggesting that increased OH-SE is accompanied by reduced DF/A and reduced avoidance behaviors.…”
Section: Discussionmentioning
confidence: 87%
“…With regards to oral health specifically, OH-SE has been positively linked to frequency of toothbrushing in children [ 13 ]. In addition, it has been shown that OHRQoL was indirectly associated with oral health knowledge through both self-efficacy and DHB [ 14 ]. Furthermore, a negative correlation between OH-SE and DF/A has been reported [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations